What is the association between price and economic activity with cigarette consumption in Cuba from 1980 to 2014?. (August 2019) - Varona-Perez, P.; Bridges, S.; Lorenzo-Vazquez, E.; Suarez-Medina, R.; Venero-Fernandez, S-J; Langley, T.; Britton, J.; Fogarty, A.W.
Abstract: Objectives: Cuba is a tobacco-producing country that has been economically isolated as a consequence of an embargo imposed by the USA. It has also experienced a severe economic depression in the 1990s after the withdrawal of support by the former Soviet Union. These characteristics provide a unique opportunity to study the relation between large changes in economic activity, cigarette price and demand for cigarettes in a relatively isolated socialist economy. Study design: This is an observational epidemiological study. Methods: Data were obtained on the annual price of a packet of cigarettes and the mean number of cigarettes consumed per adult living in Cuba from 1980 to 2014. Descriptive and regression analysis were used to explore the relationship between cigarette consumption and price in Cuba. Results: In 1980, the mean price of a packet of cigarettes was 1.53 Cuban peso (CUP) in 1997 prices and the mean annual per capita consumption was 2237 cigarettes. In 2014, the mean price had increased to 5.57 CUP (1997 prices) per packet of cigarettes, and consumption had fallen to 1527 cigarettes per capita . There were significant negative associations between annual cigarette consumption and both price and living through an economic depression. The elasticity was approximately −0.31 with price, and living through an economic depression was also associated with lower consumption of cigarettes (a reduction of 9%, 95% confidence intervals −0.18 to −0.001). Conclusions: Higher cigarette pricing, along with other public health interventions, are required to protect the national population from the adverse effects of tobacco smoke exposure. Highlights: In Cuba, there was a significant negative association between annual cigarette consumption and cigarette price with an elasticity of −0.31 Living through a period of severe economic depression was associated with a 9% decrease in cigarette consumption Higher cigarette pricing is an effective tool to decrease smoking rates in populations